1996
DOI: 10.1136/hrt.75.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin expression in endomyocardial biopsy specimens in patients with dilated cardiomyopathy: distribution along margin of fibrotic lesions.

Abstract: Objective-To examine the hypothesis that tenascin, an extracellular matrix glycoprotein, contributes to fibrotic changes in dilated cardiomyopathy. Methods-The localisation of tenascin in biopsy specimens of the hearts obtained from eight patients with dilated cardiomyopathy was examined using staining by the avidin-biotin-peroxidase complex methodResults-(1) Perimysium and endomysium. Although positive staining for tenascin was observed in the enlarged perimysium and endomysium in all patients, moderately int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…The origin of the elevated level of circulating TN-C in DCM is a matter of interest. It has been reported that expression of TN-C is observed in endomyocardial biopsy specimens of patients with DCM, 27 which strongly suggests that the serum TN-C arises from heart tissue. In the pathological myocardium, results obtained from experimental animal models, as well as human myocarditis samples, have identified that the major source of TN-C is interstitial fibroblasts.…”
Section: Discussionmentioning
confidence: 97%
“…The origin of the elevated level of circulating TN-C in DCM is a matter of interest. It has been reported that expression of TN-C is observed in endomyocardial biopsy specimens of patients with DCM, 27 which strongly suggests that the serum TN-C arises from heart tissue. In the pathological myocardium, results obtained from experimental animal models, as well as human myocarditis samples, have identified that the major source of TN-C is interstitial fibroblasts.…”
Section: Discussionmentioning
confidence: 97%
“…29 At the same time, a re-expression of tenascin in cardiac biopsies of DCM patients with a distribution pattern along the margins of fibrotic areas could be observed. 30 Some years later, the first reports occurred on significantly elevated tenascin-C serum levels in patients suffering from DCM. Aso and co-workers could demonstrate higher circulating tenascin-C levels in patients with DCM compared to controls.…”
Section: Tenascin-c In Dilated Cardiomyopathymentioning
confidence: 99%
“…TNC is re-expressed during wound healing, inflammation, regeneration, and cancer invasion [1]. In the heart, TNC is primarily expressed during cardiogenesis but reappears in the adult myocardium under various pathological conditions, including acute myocardial infarction (AMI) [2], myocarditis [3], and dilated cardiomyopathy [4]. Elevated serum levels of TNC may reflect re-expression of TNC in myocardial tissue, and the specific pathological expression pattern of myocardial TNC suggests that plasma TNC levels may be useful as a marker of left ventricular remodeling in patients with AMI, dilated cardiomyopathy or heart failure [5][6][7].…”
Section: Introductionmentioning
confidence: 99%